Luis Seoane, imágenes transatlánticas entre papeles y paredes - Dolinko, Silvia Esther (2022)
Since the late 1930s, Luis Seoane's artistic interventions in Argentina -bothwithin the Galician exile community and in his relationship with the Buenos Aires culturalfield aimed to realize an intellectual and artistic project that sought to provide accessto art to a wide audience, transcending the traditional limits of elite cultural consumption. In this project with a democratizing vocation, graphic and mural work were highlyrelevant. Taking that into consideration, there are numerous points of contact -both inthematic, as in formal and conceptual terms- between these two spheres within Seoane's vast production. This work focuses on various aspects of the artist's Buenos Airesactivity, developed between tradition and experimentation, the review of history andthe projection from modernity. It thusly aims to highlight the meanings of his printedproduction and his interventions in public art as works that sustained his intellectualprogram and his creative project.